Students bring trouble to math office
Accompanying page reads: 'STUDENTS BRING TROUBLE TO MATH OFFICE. Cal Poly maintains a full-time Math department office well staffed with able instructors and Math majors to give help or additional instructions to math students outside of class. Here Dr. Whitson, department head, explains a problem in Analytic Geometry to students Arnold Volney, Darwin Miller, and Henry Berry as instructor, Mr. McIntosh (far right background) looks on. Mr. Elston, instructor of prep and agricultural math, also gives help, in slide-rule operation, to blind G.I student, Lee Beddow, who uses a braille slide rule, and is an outstanding student in spite of his handicap. Instructor Mr. Folsom (far left foreground) answers the busy office phone.'